Employees’ perception on recruitment & selection process in Square Pharmaceuticals Ltd. - Esha, Farhana Hoque (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.